2014
DOI: 10.1097/olq.0000000000000175
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Study of Genital, Rectal, and Pharyngeal Chlamydia and Gonorrhea in Women in Rural South Africa

Abstract: Genital and rectal, but not pharyngeal, chlamydia and gonorrhea are highly prevalent and frequently asymptomatic in women in rural South Africa. Young women attending health care facilities for antenatal care or family planning should be prioritized in control efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
93
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 26 publications
4
93
1
1
Order By: Relevance
“…These observations have led to the hypothesis that long-lasting chlamydial infection in the GI tract may serve as a reservoir for reinfecting the genital tract (18). Consistent with this hypothesis are the findings that GI tract infection with Chlamydia trachomatis has been detected not only in men having sex with men (MSM) (19,20) but also in women (21).…”
supporting
confidence: 65%
See 3 more Smart Citations
“…These observations have led to the hypothesis that long-lasting chlamydial infection in the GI tract may serve as a reservoir for reinfecting the genital tract (18). Consistent with this hypothesis are the findings that GI tract infection with Chlamydia trachomatis has been detected not only in men having sex with men (MSM) (19,20) but also in women (21).…”
supporting
confidence: 65%
“…For example, a positive diagnosis for C. trachomatis in rectal swabs has been reported among diverse woman populations, some of whom may not necessarily practice oral or anal intercourse. A recent crosssectional study of 604 adult women visiting 25 primary health care facilities in rural South Africa revealed a 7.1% rate of rectal chlamydial infection (21). A separate study reported a Ͼ10% prevalence rate for rectal chlamydial infection among 3,055 women who attended 2 Canadian provincial sexually transmitted infection (STI) clinics (27).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Extra-genital CT infections are often asymptomatic or characterized by nonspecific symptoms, acting as an important reservoir for further transmission and potentially leading to sequelae both in men having sex with men (MSM) and in women (van Liere et al, 2013(van Liere et al, , 2014Peters et al, 2014;Patton et al, 2014).…”
Section: Introductionmentioning
confidence: 99%